Pengaruh Karakteristik Wirausaha, Lingkungan Eksternal dan Strategi Bertahan Umkm dalam Menjaga Keberlangsungan Usaha di Musim Pandemi Covid 19 - Dwiastanti, Anis; Mustapa, Gusnar (Universitas Negeri Semarang, 2020)
This research aims to analyze the relationship between entrepreneurial characteristics, external environment and MSME survival strategy in maintaining business continuity during pandemic period, both partially and simultaneously. The research was conducted with a quantitative approach with a sample of 128 MSMEs in Malang Raya. Regression analysis is used to test the relationship between the variables studied. The results showed a partial and simultaneous relationship between individual characteristics, external environment and MSME survival strategy in maintaining business continuity, where entrepreneurial characteristics are the dominant variables affecting business continuity. The results of this study further recommend that the need to edify the talents of interest and confidence of entrepreneurial actors to the challenges and opportunities faced with hard work and real perseverance.